2021
DOI: 10.3390/cells10040863
|View full text |Cite
|
Sign up to set email alerts
|

Role of Decorin in Posterior Capsule Opacification and Eye Lens Development

Abstract: Decorin (DCN) is involved in a variety of physiological and pathological processes. Epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs) has been proposed as a major cause for the development of posterior capsule opacification (PCO) after cataract surgery. We investigated the plausible target gene(s) that suppress PCO. The expression of Dcn was significantly upregulated in rat PCO tissues compared to that observed in the control using a microarray-based approach. LECs treated with fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Only studies on the lens found that TPM played a crucial role in maintaining lens physiology and morphology. 35 In this study, we localized TPM1 by immunohistochemistry and found that it was mainly expressed in the cribriform structure of TM. Likewise, ACTC1 and TNNT1 were also mainly expressed in the cribriform structure of TM.…”
Section: Discussionmentioning
confidence: 74%
“…Only studies on the lens found that TPM played a crucial role in maintaining lens physiology and morphology. 35 In this study, we localized TPM1 by immunohistochemistry and found that it was mainly expressed in the cribriform structure of TM. Likewise, ACTC1 and TNNT1 were also mainly expressed in the cribriform structure of TM.…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have been conducted to explore the potential therapeutic options for preventing or reversing lens fibrosis using diverse experimental models. To better validate their roles in lens transparency maintenance, in recent years, apart from in vitro studies using lens epithelial cell lines, semi-in vivo epithelial explants, the whole lens culturing, and in vivo animal models have been more widely used, including injury-induced ASC models, mock lens cataract surgery (Extracapsular Lens Extraction, ECLE) for PCO models, and transgenic/genetic knockout mice [ 19 , 52 , 53 , 54 , 55 , 56 , 57 ]. It is generally accepted that during TGF-β2-induced EMT, loss of LEC integrity is accompanied by the abnormal secretion of ECM and aberrant cell migration, resulting in fibrotic plaques and lens opacification.…”
Section: Discussionmentioning
confidence: 99%